A Comparison of iPad-Assisted and Flash Card-Assisted Instruction for Learners With Autism. Issue 2 (June 2022) - Ulzii, Davaa; Kabot, Susan; Reeve, Christine
Using electronic tablets to present flash cards for teaching skills is becoming common among practitioners. However, no published study compared the effectiveness of the electronic tablet-based flash cards to paper flash cards for teaching receptive labeling skills. The purpose of this study was to compare the efficacy of the iPad-based and paper flash cards for teaching receptive labeling to learners with autism. An adapted alternating treatments design was used. Participants included one preschool student with autism and one elementary school student with autism. Findings indicated that iPad-assisted instruction resulted in a slightly faster acquisition and slightly lower levels of prompts for both participants. No differences were found in the generalization and maintenance of the skills between the two instructional mediums. Mixed results were found for challenging behaviors associated with each intervention. Implications and suggestions for future research are discussed.